The Effect of Human Resource Competencies, Financial Inclusion, E-Commerce Implementation, and Financial Knowledge on Performance of SMES - Natariasari, Riska; Diyanto, Volta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
In the globalization era, good economic growth is an assessment of the government's success in economic development, especially in supporting programs with the concept of people's economy. The growth of SME is a government effort to increase the income of low-income groups and decrease income inequality and poverty through increasing business capacity and business management skills. The purpose of this study was to analyze the effect of human resource competencies, e-commerce implementation, financial knowledge, and financial inclusion on the performance of SMEs in Kuantan Singingi Regency. The sample used was 85 SMEs with the criteria that SMEs are registered at the Office of Cooperatives, Small & Medium Enterprises. SMEs have used E-commerce, either in the form of a platform or social media-based E-commerce, and have recorded their finances. The data collection method used purposive sampling. The analysis tool used is Warp PLS. The results of the study stated that human resource competencies affect the performance of SMEs. E-commerce implementation affects the performance of SMEs. Financial knowledge affects SME performance, while financial inclusion does not affect SME performance.